La comisión de la verdad como eje central en el conflicto armado Colombiano (2017)
The present article is a discussion of results, whose descriptive research allows us to establish what a truth commission is, as a post-conflict Colombian procedure, which is the central role of a peace dialogue and whether these commissions Truth are in accordance with international regulations, as is Protocol II of Geneva in the case of Human Rights;; In which it was possible to conclude that the agreement between the armed group FARC - EP and the Colombian Government defined the criteria of the right to the truth, justice, reparation to victims and acts of non repetition. Agreements with the standards of the Inter-American Commission on Human Rights